Optimized Platelet‐Rich Fibrin With the Low‐Speed Concept: Growth Factor Release, Biocompatibility, and Cellular Response. Issue 1 (1st January 2017) - Fujioka‐Kobayashi, Masako; Miron, Richard J.; Hernandez, Maria; Kandalam, Umadevi; Zhang, Yufeng; Choukroun, Joseph
Abstract : Background: Over the past decade, use of leukocyte platelet‐rich fibrin (L‐PRF) has gained tremendous momentum in regenerative dentistry as a low‐cost fibrin matrix used for tissue regeneration. This study characterizes how centrifugation speed (G‐force) along with centrifugation time influence growth factor release from fibrin clots, as well as the cellular activity of gingival fibroblasts exposed to each PRF matrix. Methods: Standard L‐PRF served as a control (2, 700 revolutions per minute [rpm]‐12 minutes). Two test groups using low‐speed (1, 300 rpm‐14 minutes, termed advanced PRF [A‐PRF]) and low‐speed + time (1, 300 rpm‐8 minutes; A‐PRF+) were investigated. Each PRF matrix was tested for growth factor release up to 10 days (eight donor samples) as well as biocompatibility and cellular activity. Results: The low‐speed concept (A‐PRF, A‐PRF+) demonstrated a significant increase in growth factor release of platelet‐derived growth factor (PDGF), transforming growth factor (TGF)‐β1, epidermal growth factor, and insulin‐like growth factor, with A‐PRF+ being highest of all groups. Although all PRF formulations were extremely biocompatible due to their autogenous sources, both A‐PRF and A‐PRF+ demonstrated significantly higher levels of human fibroblast migration and proliferation compared with L‐PRF. Furthermore, gingival fibroblasts cultured with A‐PRF+ demonstrated significantly higher messenger RNA (mRNA) levels of PDGF, TGF‐β, and collagen1 at either 3 or 7 days. Conclusions: The findings from the present study demonstrate modifications to centrifugation speed and time with the low‐speed concept favor an increase in growth factor release from PRF clots. This, in turn, may directly influence tissue regeneration by increasing fibroblast migration, proliferation, and collagen mRNA levels. Future animal and clinical studies are now necessary.